Magnetic levitation control based-on neural network and feedback error learning approach - Aliasghary, M.; Aliyari Shoorehdeli, M.; Jalilvand, A.; Teshnehlab, M. (IEEE, 2008)
Neural network Based controller is used for controlling a magnetic levitation system. Feedback error learning (FEL) can be regarded as a hybrid control to guarantee stability of control approach. This paper presents simulation of a magnetic levitation system controlled by a FEL neural network and PID controllers. The simulation results demonstrate that this method is more feasible and effective for magnetic levitation system control.